Primary Iris Stromal Cyst Presenting As Acute Secondary Angle Closure Glaucoma Treated with ND:YAG LASER Peripheral Iridotomy — A Rare Occurrence - Karanam Sai Rani; V. Mahathi; N. Srinivasa Rao (Delhi Journal of Ophthalmology)
A 25 year old male presented with pain, redness, sudden loss of vision in left eye with features of acute angle closure glaucoma. Ultrasound biomicroscopy showed a large single iris stromal cyst occupying the anterior chamber covering the pupil. ND:YAG laser iridotomy was done. Intraocular pressure became normal and vision improved to 6/9-. Iridocyclitis can occur in the natural course of the stromal cyst producing sudden enlargement of the cyst leading to pupillary block. To the best of our knowledge, no case has been published with large stromal cyst presenting as acute angle closure glaucoma secondary to pupillary block.